The Clinicopathological Characteristics of Alpha-Fetoprotein-Producing Adenocarcinoma of the Gastrointestinal Tract—A Single-Center Retrospective Study - Kong, Xiang-Xing; Li, Xin-Lin; Tian, Yu; Ye, Qian-Cheng; Xu, Xiao-Ming; Liu, Yue; Yang, Qi; Zhang, Li-Na; Mei, Yan-Xia; Wen, Ji-Hang; Xiao, Qian; Li, Jing-Song; et al. (Frontiers in Oncology, 2021)
AFP-producing adenocarcinoma from gastrointestinal (APA-GI) is a rare type of highly malignant tumor with poor prognosis. It may originate from any site along the GI tract with similar clinicopathological characteristics. As limited research had ever described the characteristics of APA-GI, the present article intends to systemically investigate the clinicopathological characteristics of APA-GI from a single center’s retrospective study in order to deepen the understanding of the disease. A total of 177 patients pathologically diagnosed with APA-GI between 2010 and 2017 at the Second Affiliated Hospital of Zhejiang University, School of Medicine (SAHZU) were included. And clinical data of 419 gastric cancer and 609 colorectal cancer from the TCGA database was also extracted. Clinical information of SAHZU patients was collected and a median follow-up of 14.5 months was performed to investigate clinical characteristics of APA-GI. For the pathological characteristics of APA-GI, Haematoxylin-eosin sections were reviewed and immunohistochemistry of AFP was performed. The results showed that the primary tumor could develop through the whole gastrointestinal tract, including esophagus (0.6%), stomach (83.1%), duodenum (1.1%), ileum (0.6%), appendix (0.6%), colon (5.1%) and rectum (7.9%). Hepatoid adenocarcinoma is the main pathological feature of APA-GI. AFP expression level in tumor tissue was not strictly associated with serum AFP or hepatoid differentiation. The prognosis of APA-GI was worse than that of common adenocarcinoma of gastrointestinal (CA-GI) and liver metastasis and high AFP levels suggest poor prognosis in patients with APA-GI. Therefore, the present study was the first research to systemically explored the clinicopathological characteristics of APA-GI. APA-GI occurs through the whole gastrointestinal tract with a significantly worse prognosis than CA-GI. APA-GI should be regarded as one kind of disease for its similar clinicopathological characteristics within patients.